LOW POWER RACE-FREE STATE ASSIGNMENT OF AN ASYNGHRONOUS AUTOMATON - Yu. V. Pottosin (Informatika)
The problem of a race free state assignment of an asynchronous automaton is considered. A method for the state assignment is suggested that provides the minimization of the number and theswitching activity of the memory elements along with the elimination of the critical races betweenthem.